Expression of calcium‐buffering proteins in rat intrinsic laryngeal muscles. Issue 6 (June 2015) - Ferretti, Renato; Marques, Maria Julia; Khurana, Tejvir S.; Santo Neto, Humberto
Abstract Intrinsic laryngeal muscles (ILM) are highly specialized muscles involved in phonation and airway protection, with unique properties that allow them to perform extremely rapid contractions and to escape from damage in muscle dystrophy. Due to that, they may differ from limb muscles in several physiological aspects. Because a better ability to handle intracellular calcium has been suggested to explain ILM unique properties, we hypothesized that the profile of the proteins that regulate calcium levels in ILM is different from that in a limb muscle. Calcium‐related proteins were analyzed in the ILM, cricothyroid (CT), and tibialis anterior (TA) muscles from male Sprague–Dawley rats (8 weeks of age) using quantitative PCR and western blotting. Higher expression of key Ca2+ regulatory proteins was detected in ILM compared to TA, such as the sarcoplasmic reticulum (SR) Ca2+‐reuptake proteins (Sercas 1 and 2), the Na+/Ca2+ exchanger, phospholamban, and the Ca2+‐binding protein calsequestrin. Parvalbumin, calmodulin and the ATPase, Ca2+‐transporting, and plasma membrane 1 were also expressed at higher levels in ILM compared to TA. The store‐operated calcium entry channel molecule was decreased in ILM compared to the limb muscle and the voltage‐dependent L‐type and ryanodine receptor were expressed at similar levels in ILM and TA. These results show that ILM have a calcium regulation system profile suggestive of a better ability to handle calcium changes in comparison to limb muscles, and this may provide a mechanistic insight for their unique pathophysiological properties.